1996
DOI: 10.1016/0168-6445(96)00021-6
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline resistance determinants: mechanisms of action, regulation of expression, genetic mobility, and distribution

Abstract: Tetracycline-resistant bacteria were first isolated in 1953 from Shigella dysenteriae, a bacterium which causes bacterial dysentery. Since then tetracycline-resistant bacteria have been found in increasing numbers of species and genera. This has resulted in reduced effectiveness of tetracycline therapy over time. Tetracycline resistance is normally due to the acquisition of new genes often associated with either a mobile plasmid or a transposon. These tetracycline resistance determin~mts are distinguishable bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
237
0
23

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(265 citation statements)
references
References 119 publications
(380 reference statements)
5
237
0
23
Order By: Relevance
“…The excessive use of antimicrobial drugs in human and veterinary medicine, including the administration of antibiotics as growth promoters for food animals, contributes to the emergence and dissemination of antibiotic resistance among various species of bacteria including salmonellae (Roberts 1996). In black-headed gulls, we found Salmonella strains resistant to streptomycin, sulfonamides, ampicillin, tetracycline, chloramphenicol, and nalidixic acid.…”
Section: Discussionmentioning
confidence: 98%
“…The excessive use of antimicrobial drugs in human and veterinary medicine, including the administration of antibiotics as growth promoters for food animals, contributes to the emergence and dissemination of antibiotic resistance among various species of bacteria including salmonellae (Roberts 1996). In black-headed gulls, we found Salmonella strains resistant to streptomycin, sulfonamides, ampicillin, tetracycline, chloramphenicol, and nalidixic acid.…”
Section: Discussionmentioning
confidence: 98%
“…The genes encoding for tetracycline resistance are numerous but the most widely distributed tetracycline resistance determinant in Gram-positive bacteria is the tet(M) gene (Roberts 1996). Previous studies have shown the diversity of the tet(M) gene in different bacterial strains and species (Huys et al 2004;Bertrand et al 2005;Spigaglia et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Different mechanisms are implicated in resistance against tetracycline, such as ribosome protection, encoded for example by tet(M), tet(O) and tet(S) genes, and efflux systems, encoded by tet(K) and tet(L). The widespread distribution of tet(M) in many bacterial genera, including Enterococcus (Clewell et al 1995;Roberts 1996), is often linked to the presence of conjugative transposons of the Tn916-1545 family. Mating experiments have demonstrated the ability of some Enterococcus faecalis, Enterococcus faecium and Enterococcus durans strains to transfer tetracycline resistance determinants by means of Tn916-1545 transposons (Huys et al 2004;Wilcks et al 2005;Hummel et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these transfer events may have occurred long ago on an evolutionary time scale, and the genes have subsequently diverged. Many different tet(M) genes from clinical bacterial isolates, located on various plasmids and CTns, have been sequenced and shown to diverge by between 1 [39] and 8% [47] (table 3). The nonrandom distribution of nucleotide changes illustrates the existence of mosaic genes, derived from two distinct alleles, which appear to have arisen by recombination after the gene integrated into Tn916 [47].…”
Section: Circumstantial Evidence For the Widespread Transfer Of Resismentioning
confidence: 99%